2020
DOI: 10.30872/plakat.v2i2.4974
|View full text |Cite
|
Sign up to set email alerts
|

Psikoedukasi Online Pendampingan Anak Belajar Daring Akibat Terdampak Pandemi Covid 19

Abstract: Covid19 adalah suatu penyakit menular yang disebabkan oleh jenis virus corona yang muncul awal 2020 di Indonesia. Pandemi Covid 19 telah berdampak luas pada semua sektor kehidupan tanpa terkecuali pada dunia pendidikan. Menurut informasi dari media online Republika.com disimpulkan bahwa belajar daring (dalam jaringan) menimbulkan masalah baru terutama bagi orangtua. Orangtua mengeluhkan belajar daring di rumah menambah kesibukan mereka. Wali murid merasa stres mengawasi kegiatan belajar anak di rumah karena se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Khairi (2021), webinars can make learning more effective, improve teacher quality, improve performance, and are an alternative model of friendly mentoring against the government's ban on working in offices due to the Covid 19 pandemic. Rusli et al (2020) found research results that increased parents' understanding, knowledge, and experience after attending online psychoeducation. Even in webinar counseling services, research by Duniawati et al (2020) found that online counseling services provided in the form of psychoeducational counseling services, non-interactive counseling services, and synchronous interactive counseling services are more effective in data collection, data storage, not limited to geographic and economic location.…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 93%
“…Khairi (2021), webinars can make learning more effective, improve teacher quality, improve performance, and are an alternative model of friendly mentoring against the government's ban on working in offices due to the Covid 19 pandemic. Rusli et al (2020) found research results that increased parents' understanding, knowledge, and experience after attending online psychoeducation. Even in webinar counseling services, research by Duniawati et al (2020) found that online counseling services provided in the form of psychoeducational counseling services, non-interactive counseling services, and synchronous interactive counseling services are more effective in data collection, data storage, not limited to geographic and economic location.…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 93%
“…Metode dalam pengabdian ini menggunakan metode sosialisasi secara daring karena menyesuaikan dengan kondisi pandemi (Rusli, Nio, Akbar, & Nurmina, 2020). Selain itu metode…”
Section: Metode Pelaksanaanunclassified
“…Kebijakan tersebut berisi imbauan agar masyakarat melakukan pembatasan aktivitas di luar rumah termasuk beribadah, belajar, dan bekerja, serta memindahkan berbagai kegiatan tersebut di rumah. Pemberlakuan pembatasan sosial ini menimbulkan dampak yang cukup besar dan melemahkan berbagai sektor, seperti sektor ekonomi, kesehatan, dan pendidikan (Rusli et al, 2020).…”
Section: Pendahuluanunclassified